Laboratory formation of micro-penitentes at temperatures and pressures relevant to Earth and other worlds - Daniel Floyd Berisford; Jeffrey Tyler Foster; Jacob Kosberg; Benjamin Furst; Michael Joseph Poston; Takuro Daimaru; Maggie Lang; Lavina Backman; Kevin Peter Hand (Journal of Glaciology)
We conducted a series of experiments that revealed the formation of mm-scale penitente structures in ice illuminated by broadband light under moderate vacuum conditions between 50 and 2000 Pa. The experimental apparatus consists of a 0.3 m diameter cylindrical vacuum chamber with a cooling jacket surrounding the outer radius and bottom surface. Light shines in through an optical window at the top to illuminate most of the ice surface. We observe penitente-like structures at temperatures between −15$^°$C and $-2^°$C and pressures close to the equilibrium vapor pressure at the ice surface temperature. The formation of these structures is very sensitive to slight changes in background pressure, and the structures tend to vanish with significant deviations away from the equilibrium curve, resulting in a smooth sublimated crater formation instead of penitentes. Application of the physical model by Claudin and others (2015, doi: 10.1103/PhysRevE.92.033015) at experimental conditions generally agrees with observations for penitente spacing.